Creativity and Affective Temperament in Artistic and Non‐artistic Students: Different Temperaments are Related to Different Aspects of Creativity. (12th September 2019) - Jaracz, Marcin; Borkowska, Alina
Abstract: The relationship between creativity and temperament has been well documented in studies with professional artists. This also pertains to affective temperaments which constitute the vulnerability to affective disorders. However, less is known about the contribution of particular temperaments to specific components of creativity, for example, ideational fluency, or originality of thinking. The aim of the present study was to assess affective temperaments and creativity in artistic and non‐artistic students. Ninety (39 artistic and 51 non‐artistic) students were enrolled in the study. Affective temperaments were evaluated by means of TEMPS‐A questionnaire. Creativity was measured with BWAS test assessing the originality of thinking and a sample of tasks derived from BIS battery, assessing ideational fluency. Artistic students showed higher rates of cyclothymic temperament. They also outperformed non‐artistic students in both domains of creativity. The originality of thinking correlated positively with the level of cyclothymic temperament, whereas ideational fluency was positively related to hyperthymic temperament. Ideational fluency also correlated with the level of parental education. Results indicate that creativity is related to temperaments underlying predisposition to bipolar affective disorder; however, different temperaments are related to different aspects of creativity.